Ambientalização curricular em cursos de Pedagogia de instituições privadas do município de São Paulo: desafios e proposições - Aversi, Tânia Lídia Ribeiro (2015)
The research s aim was to identify and analyze in documents, speeches and practices of pedagogy docents the challenges they face when trying to introduce environmental themes to classes for pedagogy bachelor s students as well as the propositions they created to solve such challenges. Researchers that reveal environmental curriculum processes, authors of the field of environmental education and authors of teacher s education were used as reference theory. The locus of the research were four private institutions located in São Paulo county and the reason for that is that the private sector is responsible to graduate an expressive amount of teachers who work within the region in areas such as kindergarten and the first levels of elementary school. The instruments used for collecting data were: a) analysis of official documents (pedagogic projects, curriculum and teaching plans) and technical documents (lesson plans and reports), b) interviews partially structured with pedagogy courses coordinators and teachers of disciplines that approach the environmental thematic, c) observation of teacher s pedagogic practices through watching their classes. The data analysis was based on the following categories: relevance of the environmental thematic in the education of pedagogues; political pedagogical tendencies present in methodological approaches; challenges and propositions of coordinators and professors to widen the environmental curriculum. The data analysis revealed the coexistence of conservacionista (conservative) and pragmática (pragmatic) tendencies in docents practices as well as limits related to the curricular interdisciplinarity and to the education of pedagogues oriented to work with the environmental thematic. As result the analysis has shown a list of propositions for the process of introduction of the thematic in the curriculum. It is expected that this investigation can be useful as resource for following researches and eventually for the elaboration of projects of intervention in environmental education for pedagogy students or docents